Screening de novos antivirais inibidores de flavivirus - Pacca, Carolina Colombelli (2013)
Introduction. Arboviruses, arthropod-borne viruses, are frequently associated with human outbreaks and represent a serious health problem. The genus Flavivirus, which includes both the Yellow Fever Virus (YFV) and Saint Louis Encephalitis Virus (SLEV), are important pathogens that result in high morbidity and mortality rates worldwide. In Brazil, YFV has a sylvatic cycle and occurs annually, despite the efficiency of the vaccine. Saint Louis Encephalitis is an infectious illness that can cause acute fever caused by SLEV, which is widely distributed in the Americas. The emergence of SLEV became a serious concern after the first related outbreak in Brazil in 2006, in the city of Sao Jose do Rio Preto. There is no specific antiviral drug for these viruses, only supporting treatment that can alleviate the symptoms and prevent complications. The need to develop effective and safe antiviral drugs is indispensable for the treatment of these infections. Objective. The aim of this work was to identify new possible antiviral drugs against the arboviruses that can cause acute fever and encephalitis (YFV and SLEV) and to evaluate the capacity of inhibition of these compounds in ABR mice. Material and Methods. Plaque reduction assay, flow citometry, immunofluorescence and cellular viability were used to test the compounds in vitro. ABR mice were inoculated with YFV, and the biological samples were tested for the presence of the virus through the use of plaque reduction assay and qPCR. Neutralization assay was also performed. Results. Treated cells showed efficient inhibition of viral replication at concentrations that presented minimal toxicity to the cells. The assays showed that ftalyl-tiazole and fenoxytiosemicarbazone were more effective, and that they reduced viral replication by 60% and 75% for YFV and SLEV, respectively. The analysis also revealed that the ABR mice inoculated with YFV had histopathological alterations in the liver; however, the samples did not present viral title. Neutralization assay showed a high concentration of antibodies in the serum. Conclusion. The inhibitions of viral replication were confirmed through the use of some assays in vitro, and the effectiveness of the selected compounds show that they are an option in the treatment of these viruses. More detailed studies are needed to determine the mechanism of action of these molecules. The mice were found to have histopathological alterations, which indicates viral infection; however, they also presented with high concentrations of antibodies. More studies about animal models are necessary to make in vivo experiments.